A Case Report: Post-Mortem Pathological Observations of a Fresh Dairy Cow with Type 3 Abomasal Ulcer After Sudden Death - Greta Šertvytytė; Gabija Lembovičiūtė; Osvaldas Rodaitis; Karina Džermeikaitė; Samanta Arlauskaitė; Justina Krištolaitytė; Akvilė Girdauskaitė; Alius Pockevičius; Arūnas Rutkauskas; Ramūnas Antanaitis (Animals)
In dairy cattle, abomasal ulcers are a serious but sometimes disregarded ailment that can have detrimental effects on health and cause financial losses. Due to inconclusive clinical symptoms, abomasal ulcers are typically misdiagnosed and treated improperly. Specialized diagnostic methods should be considered to ensure a correct diagnosis and the well-being of cattle. This report focuses on a 4-year-old Holstein-Friesian cow which began her third lactation two weeks before she started showing general clinical signs of an elevated fat–protein ratio in the milk and was diagnosed with an abomasum displacement. The clinical signs can also be mistaken for other conditions such as traumatic reticuloperitonitis and left dislocated abomasum. The patient was brought to the LUHS Large Animal Clinic, and after a short while, sudden death occurred. The autopsy concluded that death had occurred due to hypovolemic shock caused by abomasal ulcer perforation, which caused bleeding into the abomasum and intestines. Also, the type 3 ulcer caused severe peritonitis and anemia, and feed and fibrin could be seen on the outside of organs in the abdomen. Blood clots mixed with feed had formed in the inside of the abomasum and intestinal tract. Based on the work of previous scientific studies, it has been established that the occurrence of ulcers is more frequent in dairy cows during the first four to six weeks of lactation. And the most probable cause could be intensive feeding and dietary changes. Ulcers in the abomasum are very difficult to diagnose, because they require special diagnostic equipment such as an ultrasound or surgical interventions. Due to the similarity with other diseases, this pathological condition of the abomasum is most frequently only identified in post-mortem examinations.